E-Voting Optimization For Head Of Community Unit (RW) Election with WAPT Testing - Samudi, Samudi; Brawijaya, Herlambang; Widodo, Slamet (Sinkron : jurnal dan penelitian teknik informatika, 2019)
This conventional election has several weaknesses, including difficulties in determining the validity of ballots, the process of counting ballots is slow. From the above problems, the authors propose to design and build a system to carry out elections using information technology called Electronic Voting. The method in this study uses the waterfall method which consists of the stages of needs Communication, Planning, Modeling, Construction, dan Deployment. The results of this study are to produce elections held with the District E-Voting.